Network Analysis of Depressive Symptoms Among Residents of Wuhan in the Later Stage of the COVID-19 Pandemic - Zhao, Na; Li, Wen; Zhang, Shu-Fang; Yang, Bing Xiang; Sha, Sha; Cheung, Teris; Jackson, Todd; Zang, Yu-Feng; Xiang, Yu-Tao (Frontiers in Psychiatry, 2021)
Background: Depression has been a common mental health problem both during and following China’s COVID-19 epidemic. From a network perspective, depression can be conceptualized as the result of mutual interactions among individual symptoms, an approach that may elucidate the structure and mechanisms underlying this disorder. This study aimed to examine the structure of depression among residents in Wuhan, the epicenter of the COVID-19 outbreak in China, in the post COVID-19 era. Methods: A total of 2 515 participants were recruited from the community. The Patient Health Questionnaire was used to assess depressive symptoms. The network structure and relevant centrality indices of depression were examined in this sample. Results: Network analysis revealed Fatigue, Sad mood, Guilt and Motor disturbances emerged as the most central symptoms, while Suicide and Sleep problems had the lowest centrality. No significant differences of network structure and global strength were found between female and male participants, a finding that suggests there are no gender differences in the structure or centrality of depressive symptoms. Limitations: Due to the cross-sectional study design, causal relationships between these depressive symptoms or dynamic changes in networks over time could not be established. Conclusions: Fatigue, Sad mood, Guilt and Motor disturbances should be prioritized as targets in interventions and prevention efforts to reduce depression among residents in Wuhan, in the post COVID-19 era.